The Influence of Genes on the “Killer Plasmid” of Dinoroseobacter shibae on Its Symbiosis With the Dinoflagellate Prorocentrum minimum - Mansky, Johannes; Wang, Hui; Ebert, Matthias; Härtig, Elisabeth; Jahn, Dieter; Tomasch, Jürgen; Wagner-Döbler, Irene (Frontiers in Microbiology, 2022)
The marine bacterium Dinoroseobacter shibae shows a Jekyll-and-Hyde behavior in co-culture with the dinoflagellate Prorocentrum minimum: In the initial symbiotic phase it provides the essential vitamins B12 (cobalamin) and B1 (thiamine) to the algae. In the later pathogenic phase it kills the dinoflagellate. The killing phenotype is determined by the 191 kb plasmid and can be conjugated into other Roseobacters. From a transposon-library of D. shibae we retrieved 28 mutants whose insertion sites were located on the 191 kb plasmid. We co-cultivated each of them with P. minimum in L1 medium lacking vitamin B12. With 20 mutant strains no algal growth beyond the axenic control lacking B12 occurred. Several of these genes were predicted to encode proteins from the type IV secretion system (T4SS). They are apparently essential for establishing the symbiosis. With five transposon mutant strains, the initial symbiotic phase was intact but the later pathogenic phase was lost in co-culture. In three of them the insertion sites were located in an operon predicted to encode genes for biotin (B7) uptake. Both P. minimum and D. shibae are auxotrophic for biotin. We hypothesize that the bacterium depletes the medium from biotin resulting in apoptosis of the dinoflagellate.